Male Pseudohermaphroditism due to 5 alpha Reductase-2 Deficiency- An Uncommon Etiology (Journal of Medicine, 2009)
A 15 years adolescent male muslim presented to us with ambiguous genitalia. At birth he was identified as a female baby and since then reared as a female. At the age of 13, his parents surprisingly observed that some of his phenotypic expressions were becoming male type such as deepening of voice, appearance of facial hair, enlargement of phallus, non development of breast and failure to start menstruation. On examination, he had ambiguous genitalia with enlarged phallus with hypospadias, pigmented labioscrotal folds with blind ended vagina, and pubic hair in stage-3. He was diagnosed as a case of pseudovaginal perineoserotal hypospadias. Serum testosterone and LH level were within the normal range. Karyotyping of the patient revealed 46XY. USG of the whole abdomen revealed no mullarian duct derivatives or gonads. Laparoscopic examination showed only one gonad in the left inguinal region. History, physical examination and investigations suggested the diagnosis of male pseudohermaphroditism due to deficiency of 5 alpha reductase-2 enzyme. Key words: Male pseudohermaphroditism, 5 alpha reductase-2 deficiency.   doi: 10.3329/jom.v10i2.2834   J MEDICINE 2009; 10 : 142-145